2020
DOI: 10.2298/fil2001231e
|View full text |Cite
|
Sign up to set email alerts
|

Analytical techniques for solving the equation governing the unsteady flow of a polytropic gas with time-fractional derivative

Abstract: In this work, some analytical techniques viz. homotopy perturbation method, new iterative method and integral iterative method are used to solve nonlinear fractional differential equations such as the equation governing the unsteady flow of a polytropic gas with time-fractional derivative. Comparisons are made between the considered techniques and also between their results. The obtained results reveal that these techniques are very simple and effective and give the solution in series form which in closed form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Based on average dwell-time method, Razumikhin-type technique and vector Lyapunov function, some novel stability method are obtained for impulsive stochastic functional differential systems. On a study of different types of stability studies for FSDEs can be found in [1,4,10,17,24,30,44].…”
Section: Introductionmentioning
confidence: 99%
“…Based on average dwell-time method, Razumikhin-type technique and vector Lyapunov function, some novel stability method are obtained for impulsive stochastic functional differential systems. On a study of different types of stability studies for FSDEs can be found in [1,4,10,17,24,30,44].…”
Section: Introductionmentioning
confidence: 99%
“…Based on average dwell-time method, Razumikhin-type technique and vector Lyapunov function, some novel stability method are obtained for impulsive stochastic functional differential systems. On a study of different types of stability studies for FSDEs can be found in [2,3,4,5,24,44,45].…”
Section: Introductionmentioning
confidence: 99%